2014
DOI: 10.1111/ejed.12080
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Early‐career Support of Teachers in Europe

Abstract: IntroductionThe deep economic, social, technological and cultural changes in Europe represent a real challenge for teacher education. The teacher's role is becoming more complex and demanding, while the expectations of society are rising. Teachers are expected not only to enable optimal development of increasingly heterogeneous groups of pupils, but also to mitigate the effects of social inequality. All this requires qualitative changes in pre-service and in-service teacher education. In this regard, the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
(16 reference statements)
0
15
0
2
Order By: Relevance
“…Certain key elements are required from the mentor, and Zuljan and Požarnik (2014) highlight the importance of certain personal attributes (see also Ambrosetti and Dekkers 2010;Hudson 2004aHudson , 2004bOmeechevarria 2019) during mentoring which should be part and parcel of the mentor, such as the belief that the mentee has potential that can be nurtured, looking after the mentee's well-being, sound interpersonal and communication skills, listening and empathy, as well as a balance between supporting and challenging the mentee. System requirements such as assisting the mentee with the planning before his or her teaching, including lesson plan discussion, are also key, as are organisational skills, time management and stress management (Zuljan and Požarnik 2014). The mentor should also have sound pedagogical knowledge, and this includes classroom management, curriculum-related recommendations, advice on teaching strategies and teaching materials (Zuljan and Požarnik 2014), since being in command of one's pedagogical knowledge allows the mentor to be in command of the above-mentioned elements.…”
Section: Approaches To or Models For Mentoring And Their Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain key elements are required from the mentor, and Zuljan and Požarnik (2014) highlight the importance of certain personal attributes (see also Ambrosetti and Dekkers 2010;Hudson 2004aHudson , 2004bOmeechevarria 2019) during mentoring which should be part and parcel of the mentor, such as the belief that the mentee has potential that can be nurtured, looking after the mentee's well-being, sound interpersonal and communication skills, listening and empathy, as well as a balance between supporting and challenging the mentee. System requirements such as assisting the mentee with the planning before his or her teaching, including lesson plan discussion, are also key, as are organisational skills, time management and stress management (Zuljan and Požarnik 2014). The mentor should also have sound pedagogical knowledge, and this includes classroom management, curriculum-related recommendations, advice on teaching strategies and teaching materials (Zuljan and Požarnik 2014), since being in command of one's pedagogical knowledge allows the mentor to be in command of the above-mentioned elements.…”
Section: Approaches To or Models For Mentoring And Their Potentialmentioning
confidence: 99%
“…System requirements such as assisting the mentee with the planning before his or her teaching, including lesson plan discussion, are also key, as are organisational skills, time management and stress management (Zuljan and Požarnik 2014). The mentor should also have sound pedagogical knowledge, and this includes classroom management, curriculum-related recommendations, advice on teaching strategies and teaching materials (Zuljan and Požarnik 2014), since being in command of one's pedagogical knowledge allows the mentor to be in command of the above-mentioned elements.…”
Section: Approaches To or Models For Mentoring And Their Potentialmentioning
confidence: 99%
“…), as well as reflecting on the quality of the study process (from the cognitive as well as the conative point of view). Several researchers of higher education didactics (Biggs and Tang, 2011;Kalin and Šteh, 2015;Kalin and Valenčič Zuljan, 2015;Marentič Požarnik and Lavrič, 2015;Puklek Levpušček and Marentič Požarnik, 2005;Strmčnik, 2010;Valenčič Zuljan and Marentič Požarnik, 2014) point out that in the study process, it is important to provide problem-based and inquiry-based learning, to connect different content and include authentic challenges, as well as to consider students' pre-knowledge and facilitate students' learning skills.…”
Section: Discussionmentioning
confidence: 99%
“…Različni raziskovalci visokošolske didaktike (Biggs in Tang, 2011;Kalin in Šteh, 2015;Kalin in Valenčič Zuljan, 2015;Marentič Požarnik in Lavrič, 2015;Puklek Levpušček in Marentič Požarnik, 2005;Strmčnik, 2010;Valenčič Zuljan in Marentič Požarnik, 2014) izpostavljajo, da je v študijskem procesu pomembno zagotavljati problemsko naravnanost, učenje z odkrivanjem in raziskovanjem, povezovanje med različnimi vsebinskimi področji in avtentičnimi (življenjskimi) izzivi, da je ključno navezovanje na študentovo predznanje in razvijanje spretnosti študentovega učenja. Pomembno je torej, da študenti pridobijo poglobljeno temeljno znanje, ki ga bodo sposobni uporabiti za razreševanje novih, še neslutenih izzivov lastne stroke, da bodo sposobni svoje področje razvijati in pri tem sodelovati s strokovnjaki z istega področja kot tudi s strokovnjaki z drugih področij in širšo javnostjo.…”
unclassified
“…Supporting the importance of context over experience is the study of Wyss, Kocher and Baer (2017 [94]), who found that on average, novice and experienced teachers spent 50% of classroom time in whole class teaching -although with small but significant differences among the schools they analysed. Their study concludes that teaching concepts like personalised learning and other instructional alternatives are rare regardless of teacher experience per se, and highlights that teacher education reforms targeting innovation still have a little impact on the school practices of novice teachers.…”
Section: Box 3 Institutional Habitus and The Conditions Of The Possimentioning
confidence: 99%